Clinical Profile and Spectrum of Complications of Malaria in Hospitalized Children at a Tertiary Care Hospital - Rehmana Waris, Brekhna Aurengzeb, Syed Hashim Raza, Aimen Waris, Ramish Riaz (Journal of Rawalpindi Medical College, 2021)
Background: In children, clinical profile of malaria may vary from nearly asymptomatic disease to febrile illness leading to life threatening complications. The mortality among children is largely due to complications like cerebral malaria, severe anemia and pulmonary complications. The current study was conducted to study the clinical profile of malaria, its complications and factor associated with its complications. Methodology: This observational study was conducted at Children Hospital, PIMS from March 2018 to March 2021. All patients with positive immunochromatographic test and needing hospitalization due to unsettled fever or other troublesome symptom were included. Total 53 patients were included in the study. All patients underwent routine investigations which included ICTMP, complete blood picture, ultrasound abdomen, chest x rays, and routine urinary analysis. Severe malaria was characterized upon WHO guidelines. Patients were treated with chloroquine while those resistant to chloroquine were given artemisinin-based therapy. Data was analyzed by applying appropriate statistical tests via SPSS v 20. Results: Mean age of the patients was 5.80±3.5 years with male predominance (n=32, 60.4%). Majority of the patients had P.vivax (n=45, 84.9%) infection followed by P.falciparum (n=5, 9.4%), while 3 patients (5.7%) had positive immunochromatographic test for both P.vivax and P.falciparum. Severe malaria developed in 17 (32.1%) of the patients. Most common complication was severe anemia (n=10, 18.8%) followed by black water fever, ADEM disease, pneumonia and convulsions Patients with P.falciparum infection had higher risk (OR=8.00, P-value=0.07) of developing complication compared to P.vivax one. Conclusion: Rate of severe malaria was found to be 32.1% in children of current study which is quite high. Therefore, every child with malaria should be properly investigated for complications and treated accordingly.